Wilting Bermudagrass Improves Forage Silage Quality and Cattle Performance - William E. Kunkle (EDIS, 2004)
Bermudagrass has low levels of sugars that are fermented to lactic and other acids during ensiling. Wilting has been shown to improve the fermentation and the feeding value when levels of sugar are low. The effects of wilting on bermudagrass harvested as round bale silage were investigated in two trials. The round bale silage was compared to similar bermudagrass harvested as round baled hay. This document is AN146, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, UF/IFAS. Published October 2003.